Molecular Engineering of Layered Halide Double Perovskites: Challenges and Opportunities in Optoelectronics and Beyond - Ghasemi, Maryam; Karsili, Pelin; Mishra, Anamika; Golobostanfard, Mohammad Reza; Milić, Jovana V. (WILEY-V C H VERLAG GMBH, 2026)
Metal halide perovskites have become the leading semiconductors for new-generation optoelectronics. However, they are primarily based on toxic lead components, which pose environmental concerns. To address this critical limitation, there is an effort to design alternative lead-free halide perovskite materials. One of the emerging approaches has involved the use of layered (2D) halide double perovskite (LDP) materials incorporating tailored organic spacers within the lead-free perovskite framework based on alternative monovalent (MI) and trivalent (MIII) metal cations, such as Ag, Bi, Cu, In, and others. The interactions within the assemblies of these hybrid organic-inorganic structures define the resulting properties. The role of molecular engineering in the development of LDPs and their optoelectronic characteristics is reviewed from the perspective of molecular design, synthesis, and functionality. Their versatility and methods to synthesize LDPs are discussed, as well as emerging applications, revealing challenges, and opportunities for their utility in more sustainable perovskite optoelectronics and beyond.